New predictive factors identified by molecular study in chemoresistant human and canine mammary carcinoma cells - Lainetti, Patrícia de Faria [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Mammary disorders in dogs occur very frequently in non-neutered and older animals. The majority of these tumors are classified as malignant and the occurrence of metastases in lymph nodes and distant organs can reach 30% of all cases. Canine mammary tumors (CMTs) share similarities with women’s Breast Cancer (BC), including their spontaneous occurrence and higher incidence in older individuals, in addition to similar clinical and molecular characteristics. Although surgical removal is the standard treatment, chemotherapy is discussed as an adjuvant treatment. However, resistance to treatment is a challenge and may be related to acquired or pre-existing genetic mechanisms in tumors. Genetic mutations, such as the presence of SNPs and CNVs in DNA and miRNAs dysregulation can be involved in CMTs and BC resistance. In human BC, several studies have investigated the genetic and epigenic mechanism of chemoresistance. However, little is known about this mechanism in CMTs development and progression. Therefore, this study aimed to identify genetic changes and miRNA dysregulation associated with resistance to chemotherapy in mammary carcinoma cells from dogs and model to human BC. In the first step of this research, five cell lines were used and MDR1, BCRP, MRP1, MRP2 and MRP3 gene expression were assessed to evaluate the baseline expression of these multiple drug resistance genes. Then, these cells were subjected to an induced chemoresistance protocol using doxorubicin. The cell DNA was collected prior and after inducing treatment and subjected to a SNP microarray platform. In this step, we established a standard protocol for inducing MCTs cancer cell lines chemoresistance and identified several SNPs related to chemoresistance in vitro. Only UNESP-CM70 cells were able to induce growth in vivo. The IC50 was determined for each cell type, in the control group and in the treated group. The IC50s were UNESP-CM1 (CTRL = 7.8 μM; DOX = 0.21 μM), UNESP-CM4 (CTRL = 12.54 μM; DOX = 2.9 μM), UNESP-CM5 (CTRL = 0.04 μM; DOX = 0.57 μM), UNESP-CM70 (CTRL = 1.67 μM; DOX = 6.3 μM), UNESP- CMR1 (CTRL = 0.5 μM; DOX = 0.63 μM). Two genes related to the SNP mutations were found, ALK and RALGAPA2, which are associated with tumor progression, invasion, and metastasis. Then, we evaluated miRNAs (miR-29b, miR-146b, miR-191, miR-375) RT-qPCR in 36 CMTs tissue samples. The miR- 29b, miR-146b and miR-375 were found to be downregulated in group grade III when compared to the others groups. These miRNAs may be related to genes responsible for PI3K-AKT signaling pathways, focal adhesion and interaction with the extra-cellular matrix. It was possible to conclude that SNP mutations in ALK and RALGAPA2 genes were identified during CMT chemoresistance induction and miRNA downregulation was associated with high grande CMTs.
Estudo molecular para identificação de novos fatores preditivos em células mamárias humanas e caninas quimiorresistentes
Keywords: dog; mammary carcinoma; SNP; chemotherapy resistance; cell culture